Explorating Keywords in Technology Adoption Literature with Vos-Viewer - Silvina Husnah; Sri Andriani; Sulis Rochayatun (Jurnal Paradigma, 2025)
Adoption at the macro level using a bibliometric approach with the aid of VOSviewer " and "Return on Investment (ROI)". The analysis revealed five major research clusters: technological implementation challenges, the role of SMEs, financial performance and ROI, cost and industry, and corporate strategies. The overlay visualization indicates that emerging topics such as artificial intelligence and digital transformation are becoming more prominent in recent literature, while ROI-related discussions were more prevalent in earlier years. This study provides a comprehensive mapping of current research trends and focal points in the field of technology adoption, and identifies potential research gaps for future exploration. Keywords: Adoption Technology, Macro Level Analysis, dan VOSviewer